Misericordia, amor a los pobres, colaboración en la construcción de la “casa común” = Mercy, Love for the Poor, Collaboration in the Construction of the “Common Home” - Chica Arellano, Fernando (Isidorianum, 2016)
The present article deals with the issues of mercy, love for the poor, and the necessary collaboration to construct the surrounding world, our “common home”, on the basis of Pope Francis’s teaching, namely his Encyclical Laudato si’ and other documents such as Lumen fidei. Two of his images are taken as the starting point: planting a tree and opening a door. The preferential option for the poor is the common denominator, in this case as related to ecology and the protection of the environment. Pollution, climatic change, and what the Pope calls “the throwaway culture” mostly affect those most needed. Pope Francis delves into the roots of the problem and proposes some pedagogical principles in the light of the “Gospel of creation”, which are discussed in detail in this article. The conclusion is an appeal to “ecological conversion”., El presente artículo aborda los temas de la misericordia, el amor a los pobres y la colaboración en la construcción del mundo que nos rodea, o “casa común”, a la luz de las enseñanzas del Papa Francisco, concretamente en su Carta encíclica Laudato si’ y otros documentos como Lumen fidei. Dos imágenes suyas sirven de punto de partida: plantar un árbol y abrir una puerta. La opción preferencial por los pobres es el denominador común, en este caso en relación con la ecología y la protección del medio ambiente. La contaminación, el cambio climático y la “cultura del descarte” afectan en primer lugar a los más necesitados. El Papa profundiza en las raíces del problema y propone algunos principios pedagógicos, a la luz del “Evangelio de la creación”, que se discuten en detalle en este artículo. Se concluye con la llamada a la “conversión ecológica”.